A Study on Physical Parameters of Pb-Se-Te-Bi System for Optical Memory Devices - Gupta, Shilpa; Agarwal, Manuj Kumar; Saxena, Manish (International Journal of Computer Sciences and Engineering, 2019)
The Chalcogenide glasses, in last couple of decades, have got a lot of attention because of their promising potential in studies of phase change optical storage media as well as due to interesting structural, physical, electrical, optical and thermal parameters. However, there is a general trend of using some amorphous materials instead of even very carefully prepared crystalline materials, in much needed investigation of such useful chalcogenide based materials. In the present study, the impact of bismuth (Bi) concentration variation on some important physical properties of Pb10Se80-xTe10Bix (x=2, 4, 6, 8, 10, 12, 14, 16 at. %) glassy alloys has been investigated theoretically. Almost all the parameters, studied here, have been found to vary linearly with increase in Bi concentration, thus making this suitable for phase change optical recording and find applications in rewritable optical recording storage media.